Intergenerational Transmission of Cultural Values in Bicultural Families - Namjoo, Farhad; Herawati, Netty; Bhat, Rizwan Hassan (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: The objective of this study is to explore the intergenerational transmission of cultural values within bicultural families, focusing on how these families preserve their cultural heritage, adapt to their host society, and navigate the associated challenges. Methods: This qualitative research employed semi-structured interviews with 21 participants from diverse bicultural backgrounds. Participants were selected using purposive sampling to ensure a variety of cultural perspectives. Data collection continued until theoretical saturation was reached. The interviews were transcribed and analyzed using NVivo software, following a thematic approach to identify patterns and themes related to cultural value transmission. Results: The analysis revealed three main themes: preservation of cultural practices, adaptation and integration, and challenges and negotiations. Cultural preservation was achieved through traditional ceremonies, language use, cuisine, arts and crafts, and dress. Adaptation involved blending cultures, educational influences, social interactions, and media use. Challenges included generational conflicts, identity issues, discrimination, acculturation stress, balancing preservation with change, and economic factors. These findings align with existing literature on biculturalism and cultural transmission. Conclusion: The study highlights the complex dynamics of cultural value transmission in bicultural families, emphasizing the importance of supportive societal structures and policies. The findings suggest that family therapists, educators, and policymakers should consider these dynamics to effectively support bicultural families in maintaining their cultural heritage while adapting to their host society. Future research should expand on these findings by exploring additional variables and employing longitudinal designs.